Regular semantic realational principles as used in the analysis of metaphor and metonymy in Mario Eric Gamalinda's three poems - Sangalang, Josielyn Escamis (College of Arts and Letters, University of the Philippines Diliman, 1993)
This study titled regular semantic relational principles as used in the analysis of metaphor and metonymy in Mario Eric Gamalinda's three poems seeks to objectively explain metaphor and metonymy. It likewise seeks to study the three poems of Mario Eric Gamalinda, namely: "old Woman", jeepney driver along the Lealtad-Quaipo route", and "red, white and blue". Finally, it seeks to support the theory proposed by Neal R. Norrick in Semiotic principles in Semantic theory (1981) which outlines five metaphoric and 17 metonymic relational principles, saying that these would enrich semantic theory. The findings of the study prove to be encouraging. It shows that relational principles could be used in analyzing metaphors and metonymies as well as texts. Because of this, the study is able to prove that relational principles qualify to be included in semantic theory., at least findings is most significant inasmuch as it might spell solution for the many problems of language use ang usage.